What Makes You Blow You’re Whistle? the Perspectives of Public Sector - Abdullah Sani, Noridayu; Yaakup, Kausar; Azman, Hartini; Adibah Bukari, Najwa; Hui Li, Yow (International Journal of Engineering and Technology, 2018)
The objective of this study was to determine the influence of self-efficacy on WB (whistleblowing) intention. This study also examines the potential difference of employees WB intention based on age and gender. The results of this study are expected to enhance the development of ethics education module related to reporting misconduct in public sector organizations. Based on four dimensions of self-efficacy (mastery experiences, vicarious experiences, social persuasive and physiological and emotional status), the influence of each dimensions on WB intention were analyzed. The extent of self-efficacy influence on WB intention was carried out using multiple regressions that predict the likelihood to whistleblow. Evidence on any significant difference at the employees WB intention based on age and gender was identified by comparing several means (one-way ANOVA) and comparing two means (independent t-test) accordingly. The results revealed that self-efficacy influences WB intention which master experiences demonstrated the strongest positive relationship. Furthermore, there is a significant effect of age on WB intention that concludes older employees are more likely to be a whistleblower as compared to younger employees. However, there is no significant difference at the employees WB intention based on gender that proved male or females are likely to blow their whistle.Â Â